Orthoparahydrogen catalyst and preparation method thereof

By using weak crystalline crystal hydrated iron oxide and water-soluble phenolic resin, the problems of low specific surface area, insufficient strength and high wear of the existing catalysts are solved, and efficient conversion of the positive secondary hydrogen is achieved, which is suitable for the production and storage of liquid hydrogen.

CN119771507AActive Publication Date: 2025-04-08CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311279579.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-07
Publication Date
2025-04-08
Estimated Expiration
2043-10-07

AI Technical Summary

Technical Problem

The existing secondary hydrogen conversion catalyst has a low specific surface area, insufficient particle strength and high wear, resulting in poor performance in liquid hydrogen production and storage.

Method used

The catalyst is prepared by combining ultrasonic and mechanical dispersion by using weakly crystalline crystalline hydrated iron oxide and water-soluble phenolic resin as raw materials, and formed by thermal curing reaction to form a positive secondary hydrogen catalyst with high specific surface area, strength and low wear.

Benefits of technology

It improves the specific surface area and physical strength of the catalyst, reduces wear, enhances the catalytic activity of positive secondary hydrogen conversion, and is suitable for efficient production and storage of liquid hydrogen.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771507A_ABST
    Figure CN119771507A_ABST
Patent Text Reader

Abstract

The invention discloses an ortho-parahydrogen conversion catalyst and a preparation method thereof. The ortho-parahydrogen catalyst provided by the invention comprises the following components based on the weight of the catalyst: 10wt%-30wt% of phenolic resin and 70%-90% of hydrated iron oxide, wherein the hydrated iron oxide is in a weak crystal state, and the microscopic particle size is 3-10nm. The preparation method of the ortho-parahydrogen catalyst comprises the following steps: (1) preparing weakly-crystallized crystalline ferric oxide hydrate; and (2) mixing the weakly-crystallized crystalline hydrated iron oxide powder with a phenolic resin aqueous solution to form a plastic body, then carrying out extrusion molding, and carrying out a thermocuring reaction to obtain the ortho-parahydrogen catalyst. The ortho-parahydrogen catalyst is large in specific surface area, high in physical strength, small in abrasion, simple in preparation method, low in reaction temperature, small in energy consumption, high in preparation efficiency and high in ortho-parahydrogen conversion catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic conversion of ortho-parahydrogen, and in particular relates to an ortho-parahydrogen catalyst and a preparation method thereof. Background Art

[0002] Hydrogen is an ideal clean energy source. It is currently mainly used as a propellant for launch vehicles and has broad application prospects in the field of hydrogen fuel cells. As a fuel and an important energy carrier, liquid hydrogen is an ideal way to use and store hydrogen. The production of liquid hydrogen is one of the important links in the development and application of hydrogen energy.

[0003] Due to the difference in nuclear spin and the limitation of symmetry, hydrogen molecules present two different types, namely ortho-H2 and para-H2. Ortho-H2 refers to a hydrogen molecule composed of two hydrogen atoms with the same nuclear spin direction, while para-H2 refers to a hydrogen molecule composed of two hydrogen atoms with opposite nuclear spin directions. At high temperatures, the equilibrium composition of the ortho-para state remains unchanged. At room temperature, hydrogen is composed of 25% ortho-H2 and 75% para-H2. At low temperatures, the equilibrium composition of the ortho-para state will change with temperature. At the standard boiling point of liquid hydrogen, the para-H2 content can reach 99.8%. During the liquefaction of hydrogen, if the ortho-para-H2 is not catalytically converted, the liquid hydrogen produced is normal hydrogen. Liquid normal hydrogen will spontaneously undergo ortho-para conversion and eventually reach equilibrium hydrogen at the corresponding temperature. The ortho-para conversion of hydrogen is an exothermic reaction, and the heat released exceeds the latent heat of vaporization of liquid hydrogen, which will cause the vaporization loss of liquid hydrogen. Therefore, in the process of hydrogen liquefaction, multi-stage para-hydrogen conversion must be carried out, and the development of high-performance para-hydrogen conversion catalysts is crucial for the production and storage of liquid hydrogen.

[0004] Currently, amorphous hydrated iron oxide is mainly used as a catalyst for the conversion of ortho-parahydrogen.

[0005] CN202210029537.5 provides a method for preparing nano-hydrated iron oxide with high crystallinity by hydrothermal method. However, the microscopic particle size of the catalyst is 15-25 nm, the particle size is relatively large, and the specific surface area is low.

[0006] CN201910782910.2 discloses a method for preparing hydrated iron oxide, which uses a weak base as a precipitant, ferric chloride as a reactant, and disperses the product in an ammonium bicarbonate solution, filters, and dries to obtain hydrated iron oxide. This method uses the pore-forming effect of ammonium bicarbonate pyrolysis to increase the specific surface area of ​​the product, but it will cause a significant decrease in the strength of the dried particles, resulting in high abrasion of the catalyst particles.

[0007] CN202111354244.6 discloses a method for preparing a doped ortho-parahydrogen conversion catalyst by a high-temperature hydrothermal method. The method drips a metal ion solution to be doped into an iron salt solution in a certain proportion, then adds an appropriate amount of alkali solution, obtains a precipitate through a hydrothermal reaction, and then obtains a hydrated iron oxide catalyst through washing, drying and grinding. However, the high-temperature reaction time used in this preparation method is too long, the synthesis efficiency is low, the energy consumption is high, the obtained doped iron oxide grain size is large (300-1000nm), the product has high crystallinity, small specific surface area, and high abrasion of the formed particles.

[0008] CN202210832769.4 discloses a Fe atom-doped fiber magnetic catalyst FeMnO x A method for preparing a catalyst for ortho-parahydrogen conversion. The method uses a hydrothermal reaction, which has high energy consumption, and because a manganese oxide precursor needs to be prepared, the preparation cost is also high. The catalyst has a fibrous structure with a diameter of 2 to 5 nm and a length of 100 nm to 500 nm, and the product particle size is large and the specific surface area is low.

[0009] [Progress in Fine Petrochemicals, 2010, 11 (7): 26-31] The effect of the order of adding iron salt and alkali on the physical properties of iron hydroxide products was investigated. The results showed that the specific surface area of ​​the product obtained by adding alkali solution to iron salt solution was lower than that of the product obtained by adding iron salt solution to alkali solution, and the specific surface area of ​​both products was less than 150m 2 / g.

[0010] Specific surface area, particle strength and abrasion are important control indicators of catalytic materials. The hydrated iron oxide used in the above-mentioned para-hydrogen conversion catalyst has a low specific surface area, or weak particle strength and high abrasion, which is not conducive to improving the performance of the para-hydrogen conversion catalyst. Summary of the invention

[0011] In view of the deficiencies of the prior art, the present invention provides a para-hydrogen conversion catalyst and a preparation method thereof. The para-hydrogen conversion catalyst of the present invention has a large specific surface area, high physical strength, low abrasion, a simple preparation method, a low reaction temperature, low energy consumption, high preparation efficiency, and high catalytic activity for para-hydrogen conversion.

[0012] The ortho-parahydrogen catalyst of the present invention comprises the following components, based on the weight of the catalyst: 10wt% to 30wt% of phenolic resin and 70% to 90% of hydrated iron oxide; wherein the hydrated iron oxide is in a weakly crystalline state and has a microscopic particle size of 3 to 10nm; The ortho-parahydrogen catalyst of the present invention has the following properties: radial crushing strength of particles is 10-30 N / mm, abrasion is 0.05%-0.18%; specific surface area is 150-250 m 2 / g; particle diameter 1.0~2.5mm.

[0013] In the ortho-parahydrogen catalyst of the present invention, the weakly crystalline state has the following characteristics: (1) in the XRD spectrum, the peak intensity of all characteristic diffraction peaks is compared with the baseline intensity at the position (2θ), and there is no diffraction peak whose ratio is greater than 2 and whose half-height width of the diffraction angle 2θ is less than 2°; (2) there are discernible lattice fringe images in the high-magnification (200,000 times and above) transmission electron microscope images or discernible diffraction spots or diffraction rings in the electron diffraction spectrum.

[0014] The preparation method of the ortho-parahydrogen catalyst of the present invention comprises the following contents: (1) Preparation of weakly crystalline hydrated iron oxide; (2) Weakly crystalline hydrated iron oxide powder is mixed with a phenolic resin aqueous solution to form a plastic, which is then extruded into strips and subjected to a thermal curing reaction to obtain a para-hydrogen catalyst.

[0015] In the method of the present invention, the preparation process of the weakly crystalline hydrated iron oxide described in step (1) is as follows: under the simultaneous action of ultrasonic dispersion and mechanical dispersion, the iron salt solution and the inorganic alkali solution are mixed to form a colloidal mixture, and then the colloidal mixture is allowed to stand for 0.5 to 5 hours, washed, separated, dried, and then crushed and sieved to obtain weakly crystalline hydrated iron oxide powder with a certain mesh size.

[0016] Wherein, further, the iron salt is ferric chloride and / or ferric sulfate; the iron salt solution is Fe 3+ The calculated concentration is 0.10 to 1.5 mol / L, preferably 0.20 to 1.0 mol / L.

[0017] Furthermore, the inorganic alkali is one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate or ammonium bicarbonate, preferably sodium hydroxide or potassium hydroxide; the concentration of the inorganic alkali solution is OH - The calculated concentration is 0.5 to 2.0 mol / L, preferably 1.0 to 1.5 mol / L.

[0018] Furthermore, the iron salt solution is Fe 3+ Calculate with inorganic alkali solution to OH - Gage, OH - / Fe 3+ The molar ratio is 3.0 to 4.5.

[0019] Furthermore, the ultrasonic dispersion conditions are: ultrasonic frequency 20-100kHz, ultrasonic power density acting on the reaction material is 20-1200W / L, and ultrasonic dispersion temperature is 10-45°C; the preferred conditions for ultrasonic dispersion are: ultrasonic frequency 40-80KHz, ultrasonic power density 40-600W / L, and ultrasonic dispersion temperature is maintained at 20-35°C.

[0020] Furthermore, the mechanical dispersion includes but is not limited to any method and operating conditions that are conducive to rapid and uniform mixing of materials, such as mechanical stirring, magnetic stirring, shaking table, shear stirring, etc.

[0021] Furthermore, the separation is carried out by natural sedimentation, centrifugation, vacuum filtration or filter pressing to separate the washed suspension into solid and liquid to obtain a solid phase.

[0022] Furthermore, the degree of washing and filtering must satisfy the requirement that the mass content of sodium in the final catalyst composition, calculated as Na2O, is less than 0.1%, preferably the Na2O content is less than 0.01%; deionized water is generally used for washing operations.

[0023] Furthermore, the drying conditions are: drying temperature 20-60°C, drying to a water content of no more than 40wt%, preferably 10wt%-25wt%. The drying, the water content of the hydrated iron oxide is defined as: taking 5 grams of washed hydrated iron oxide, placing it in an oven at 120°C, and drying it in an air atmosphere for 12 hours, at which time the sample is set to have a water content of 0.

[0024] Furthermore, the pulverization can be carried out by various means, such as rolling, ball milling, etc. The pulverization process should keep the powder from undergoing crystal form changes, and a powder with a mesh size of 200 to 800 is further preferred.

[0025] In the method of the present invention, the mass percentage of the phenolic resin aqueous solution in step (2) is 10wt% to 70wt%, preferably 20wt% to 50wt%.

[0026] In the method of the present invention, the phenolic resin described in step (2) should be ensured to be fully mixed with the hydrated iron oxide powder, and its viscous state is suitable for extrusion molding using an extruder, generally in the shape of strips, which can be clover, four-leaf clover or cylindrical, and the diameter of the final strip is 1.0-2.5 mm, preferably 1.2-2.0 mm. The phenolic resin described is a water-soluble phenolic resin, and the phenolic resin aqueous solution can be prepared by itself or a commercial product. In the method of the present invention, the thermal curing conditions described in step (2) are: temperature of 120-160°C, time of 6-36 hours, generally carried out in an air atmosphere. The use of the para-hydrogen catalyst of the present invention in the para-hydrogen conversion reaction, the reaction conditions are: reaction temperature of 20-80K, volume space velocity of 200-2000min -1 , preferably 400~1800min -1 .

[0027] The present invention uses weakly crystalline hydrated iron oxide and water-soluble phenolic resin as raw materials, and can be formed at a relatively low temperature to obtain an aqueous solution for mixed forming, so as to maximize the catalytic activity of the active component of iron oxide, increase the effective contact area between hydrogen molecules and the catalyst, and at the same time, the catalyst has high strength and low wear, and is very suitable for normal-parahydrogen conversion reaction. The present invention does not use a high-temperature hydrothermal synthesis method, has a low reaction temperature, low energy consumption, and greatly reduces production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a transmission electron microscope image of the hydrated iron oxide prepared in Example 1.

[0029] Figure 2 This is the X-ray diffraction spectrum of the hydrated iron oxide prepared in Example 1. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with the examples. The Na2O content in the catalyst is tested by XRF method; the specific surface area is tested by low temperature nitrogen adsorption method, and the specific surface area value is calculated according to BET method; the nanoparticle size and lattice image of hydrated iron oxide are observed by transmission electron microscopy; the radial crushing strength of the molded sample is measured by HG / T The method for determining the mass content of hydrated iron oxide is defined as follows: take 5g of sample and 50mL of 25% hydrochloric acid, place them in a 250mL conical flask, heat and reflux at 60℃ for 1h, filter out the undissolved phenolic resin, dry and weigh, and calculate the mass content of hydrated iron oxide; the method for determining the degree of crystallinity of the sample is defined as follows: (1) For strongly crystalline samples, in its XRD spectrum, there is at least one diffraction peak with a ratio greater than 2 compared with the baseline intensity at the position (2θ), and the half-height width of the diffraction angle 2θ is less than 2º; (2) For weakly crystalline samples, there is no diffraction peak in its XRD spectrum that meets the above-mentioned strong crystallinity determination conditions, but there should be a discernible lattice fringe image in the high-magnification transmission electron microscope image, or there should be a discernible diffraction spot or diffraction ring in the electron diffraction spectrum. The parahydrogen content is calculated by gas chromatography. Among them, the water-soluble phenolic resin was purchased from Meisheng Engineering Plastics Company. Example 1

[0031] Prepare 1.2 mol / L sodium hydroxide solution and 0.9 mol / L ferric chloride solution respectively. At room temperature (25°C), under the conditions of mechanical stirring and ultrasonic dispersion (60kHz, 30W / L), add a certain amount of sodium hydroxide solution to the ferric chloride solution to meet the OH - / Fe 3+The molar ratio is 3.2, and a suspension is formed. After standing for 2 hours, it is repeatedly washed with water and filtered to remove impurity ions in the sample. The washings are dried in a blast oven at 40°C until the water content is about 15%. It is crushed with a pulverizer, and 300-200 mesh powder is screened. 35wt% water-soluble phenolic resin is added, and after mixing, it is formed into a strip clover shape using an extruder. Then it is dried at 140°C for 12 hours.

[0032] There are no obvious diffraction peaks in the sample's X-ray diffraction spectrum, indicating that the degree of crystallinity is not high, but obvious lattice fringes can be observed in the transmission electron microscope image with a magnification of 400,000 times, and some diffraction spots are also shown in the selected area electron diffraction spectrum, indicating that the obtained hydrated iron oxide is weakly crystalline.

[0033] The catalyst particle diameter is 1.4 mm, the radial crushing strength is 24.3 N / mm, and the specific surface area is 197 m 2 / g. The mass content of hydrated iron oxide is 83%, and the attrition is 0.10%. The hydrated iron oxide is in a weak crystalline state, and the microscopic particle size is 6.8nm. The normal-parahydrogen conversion performance test is shown in Table 1. Example 2

[0034] Prepare 1.5 mol / L sodium hydroxide solution and 1.3 mol / L ferric chloride solution respectively. At room temperature (30°C), under the conditions of mechanical stirring (300 rpm) and ultrasonic dispersion (100 KHz, 160 W / L), add a certain amount of ferric chloride solution to the sodium hydroxide solution to meet the OH content in the system. - / Fe 3+ The molar ratio is 3.2, forming a suspension. After standing for 4 hours, the sample is repeatedly washed and filtered with water to remove the sodium ions in the sample to meet the index requirements. The washings are dried in a blast oven at 60°C to a water content of about 10%, crushed with a pulverizer, 600-500 mesh powders are screened, 25wt% water-soluble phenolic resin is added, mixed and extruded into a strip-shaped four-leaf clover shape. Then dried at 150°C for 10 hours.

[0035] The test results show that the obtained hydrated iron oxide is weakly crystalline, with a catalyst particle diameter of 1.2 mm, a radial crushing strength of 22.1 N / mm, and a specific surface area of ​​202 m 2 / g. The mass content of hydrated iron oxide is 85%, the attrition is 0.13%, and the microscopic particle size is 6.2nm. The normal and para hydrogen conversion performance test is shown in Table 1. Example 3

[0036] Prepare 1.0 mol / L sodium carbonate solution and 0.6 mol / L ferric chloride solution respectively. At 45°C, under the conditions of mechanical stirring (300 rpm) and ultrasonic dispersion (80 kHz, 120 W / L), add a certain amount of sodium hydroxide solution to the ferric chloride solution to meet the OH - / Fe 3+ The molar ratio is 3.2, and a suspension is formed. After standing for 0.5 hours, the suspension is repeatedly washed and filtered with water to remove the sodium ions in the sample to meet the index requirements. The washings are dried in a blast oven at 60°C to a water content of about 13%, crushed with a pulverizer, and 500-400 mesh powders are screened. 30wt% water-soluble phenolic resin is added and formed into strip columns. Then it is dried at 160°C for 8 hours.

[0037] The test results show that the obtained hydrated iron oxide is weakly crystalline, with a catalyst particle diameter of 1.0 mm, a radial crushing strength of 20.3 N / mm, and a specific surface area of ​​212 m 2 / g. The mass content of hydrated iron oxide is 89%, the attrition is 0.15%, and the microscopic particle size is 5.7nm. The normal and para hydrogen conversion performance test is shown in Table 1. Comparative Example 1

[0038] The preparation conditions were the same as those in Example 1, except that a large amount of water-soluble phenolic resin was added, and the phenolic resin content was 45 wt %. It was found that the extrusion molding could not be performed due to the excessive amount of phenolic resin. After direct drying without extrusion molding, the specific surface area of ​​the product was only 105 m 2 / g, too much phenolic resin also damages the pore structure of the material, which is not conducive to catalytic application. The normal and para-hydrogen conversion performance test is shown in Table 1. Comparative Example 2

[0039] The preparation conditions are the same as those in Example 1, except that a certain amount of clay is added, and after mixing, a strip extruder is used to form the strip into a clover shape. After testing, the obtained hydrated iron oxide presents a weak crystalline state, the catalyst particle diameter is 1.5 mm, the radial crushing strength is 8.4 N / mm, and the specific surface area is 220 m 2 / g. The mass content of hydrated iron oxide is 82%, the attrition is 0.19%, and the microscopic particle size is 6.5nm. The normal and para-hydrogen conversion performance test is shown in Table 1. Comparative Example 3

[0040] Iron oxide was prepared according to the method provided in Example 1 of CN202210029537.5. The iron oxide grain size was 23 nm and the crystallinity was high. After testing, its specific surface area was only 66 m 2 / g. It was pressed into 1mm thick tablets and slightly crushed. The normal and para hydrogen conversion performance test is shown in Table 1. Comparative Example 4

[0041] Hydrated iron oxide was prepared according to the method of Example 3 of CN201910782910.2. After testing, the obtained hydrated iron oxide was amorphous crystalline, with an average particle size of 5.4 nm and a specific surface area of ​​238 m 2 / g. Phenolic resin was added and molded according to the method and conditions of Example 1. The resulting catalyst particles had a diameter of 1.5 mm, a radial crushing strength of 17.2 N / mm, and a specific surface area of ​​212 m 2 / g, the mass content of hydrated iron oxide is 85%, and the attrition is 0.17%. The normal and para hydrogen conversion performance test is shown in Table 1.

[0042] Table 1 Parahydrogen conversion rate of catalysts Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Parahydrogen conversion rate % 97.7 98.3 98.9 86.8 98.2 84.7 96.3 Test conditions: Activation conditions: 130℃ vacuum drying for 12h, evaluation temperature 77K, volume space velocity 400min -1 .

Claims

1. A parahydrogen catalyst, characterized in that: The catalyst weight is used as a basis, and the following components are included: 10wt%~30wt% of phenolic resin and 70%~90% of hydrated iron oxide; wherein the hydrated iron oxide is in a weakly crystalline state, and the microscopic particle size is 3-10nm.

2. The catalyst according to claim 1, characterized in that: The radial crushing strength of the particles is 10-30N / mm, and the abrasion is 0.05%-0.18%.

3. The catalyst according to claim 1, characterized in that: Specific surface area is 150~250m 2 / g; particle diameter is 1.0~2.5mm.

4. The catalyst according to claim 1, characterized in that: The weakly crystalline state has the following characteristics: (1) in the XRD spectrum, the peak intensity of all characteristic diffraction peaks is compared with the baseline intensity at the position (2θ), and there is no diffraction peak whose ratio is greater than 2 and whose half-height width of the diffraction angle 2θ is less than 2°; (2) there are discernible lattice fringe images in the high-magnification (200,000 times and above) transmission electron microscope image or discernible diffraction spots or diffraction rings in the electron diffraction spectrum.

5. A method for preparing the ortho-parahydrogen catalyst according to any one of claims 1 to 4, characterized in that The method comprises the following contents: (1) preparing weakly crystalline hydrated iron oxide; (2) mixing weakly crystalline hydrated iron oxide powder with a phenolic resin aqueous solution to form a plastic, and then extruding the plastic into strips, and performing a thermal curing reaction to obtain a para-hydrogen catalyst.

6. The method according to claim 5, characterized in that: The preparation process of the weakly crystalline hydrated iron oxide described in step (1) is as follows: under the simultaneous action of ultrasonic dispersion and mechanical dispersion, the iron salt solution and the inorganic alkali solution are mixed to form a colloidal mixture, and then the colloidal mixture is allowed to stand for 0.5 to 5 hours, washed, separated, dried, and then crushed and sieved to obtain weakly crystalline hydrated iron oxide powder of a certain mesh size.

7. The method according to claim 6, characterized in that: The iron salt is ferric chloride and / or ferric sulfate; the iron salt solution is Fe 3+ The calculated concentration is 0.10 to 1.5 mol / L, preferably 0.20 to 1.0 mol / L.

8. The method according to claim 6, characterized in that: The inorganic alkali is one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate or ammonium bicarbonate; the concentration of the inorganic alkali solution is OH - The calculated concentration is 0.5 to 2.0 mol / L, preferably 1.0 to 1.5 mol / L.

9. The method according to claim 6, characterized in that: The iron salt solution is Fe 3+ Calculate with inorganic alkali solution to OH - Gage, OH - / Fe 3+ The molar ratio is 3.0 to 4.

5.

10. The method according to claim 6, characterized in that: The ultrasonic dispersion conditions are as follows: ultrasonic frequency is 20-100kHz, ultrasonic power density acting on the reaction material is 20-1200W / L, and ultrasonic dispersion temperature is 10-45°C.

11. The method according to claim 6, characterized in that: The drying conditions are: drying temperature 20-60° C., drying to a water content of no more than 40wt%, preferably 10wt%-25wt%.

12. The method according to claim 5, characterized in that: The mass percentage of the phenolic resin aqueous solution in step (2) is 10wt%~70wt%, preferably 20wt%~50wt%.

13. The method according to claim 5, characterized in that: The phenolic resin in step (2) should be sufficiently mixed with the hydrated iron oxide powder to be in a viscous state suitable for extrusion molding using an extruder, generally in the form of strips, which may be in the form of a three-leaf clover, a four-leaf clover or a cylinder, and the diameter of the strips finally obtained is 1.0 to 2.5 mm, preferably 1.2 to 2.0 mm. The phenolic resin is a water-soluble phenolic resin, and the phenolic resin aqueous solution can be prepared by itself or a commercial product.

14. The method according to claim 5, characterized in that: The heat curing conditions of step (2) are: temperature of 120 to 160° C., time of 6 to 36 hours, and performed in an air atmosphere.

15. Use of the para-hydrogen catalyst according to any one of claims 1 to 5 in a para-hydrogen conversion reaction, characterized in that: The reaction conditions are: reaction temperature 20-80K, volume space velocity 200-2000min -1 , preferably 400~1800min -1 .

Citation Information

Patent Citations

  • Preparation method of hydrated iron oxide

    CN110422886A

  • Nano hydrated iron oxide as well as preparation method and application thereof

    CN114314677A

  • A catalyst for converting normal and para hydrogen suitable for wide range of low temperature conditions and preparation method thereof

    CN115920919B

  • Nanometer iron trioxide as well as preparation method and purpose of nanometer iron trioxide

    CN102897847A

  • Preparation method of gamma-FeOOH catalyst and special device and application

    CN107051460A